The Mediterranean Diet as a Source of Natural Compounds: Does It Represent a Protective Choice against Cancer? - Giuseppina Augimeri; Daniela Bonofiglio (MDPI AG, 2021)
The Mediterranean diet (MD), characterized by a high intake of fruits, vegetables, legumes, nuts and grains, a moderate intake of red wine and a reduced consumption of meat, has been considered one of the healthiest dietary patterns worldwide. Growing evidence suggests an inverse relationship between high adherence to the MD and cancer, as well as other chronic degenerative diseases. The beneficial effects elicited by the MD pattern on cancer are due to the high contents of bioactive compounds contained in many foods of MD, which protect cells by oxidative and inflammatory processes and inhibit carcinogenesis by targeting the various hallmarks of cancer with different mechanisms of action. Although over the past decades numerous dietary and phytochemical compounds from Mediterranean food that have anticancer potential have been identified, a clear association between the MD eating pattern and cancer needs to be established. While we wait for answers to this question from well-conducted research, the empowering of the MD as a protective choice against cancer should represent the priority for public health policies.